PERLINDUNGAN HUKUM BAGI KONSUMEN YANG MENGALAMI KERUGIAN AKIBAT PENGIRIMAN BARANG DARI PERUSAHAAN EKSPEDISI - Nurul Baytih; Ma'ruf Hafidz; Salmawati (Qawanin Jurnal Ilmu Hukum, 2020)
This research aims to find out and understand how legal protection for consumers who suffer losses due to the delivery of goods from shipping companies and how the liability of shipping companies to consumers who suffer losses due to the delivery of goods. This research uses empirical methods. The location of the research was conducted in one of the expedition companies precisely in PT. Tiki Line Nugraha Ekakurir (JNE) Watampone branch. Types and sources of data used are primary data and secondary data with data collection techniques, namely field research with interview techniques and literature research. The data obtained will be processed and analyzed to produce conclusions and submitted descriptively to provide a clear understanding of the results of research conducted by the author. The results of this study show legal protection for consumers against losses due to the delivery of goods from shipping companies, namely by referring to some provisions stated in Law No. 8 of 1999 on Consumer Protection and one form of liability of shipping companies that is by providing replacement shipping rates for domestic shipments and international shipments which form of liability including through presumption to always be responsible.